Association of selected adipokines with metabolic syndrome and cardio-metabolic risk factors in young males. (September 2020) - Ouerghi, Nejmeddine; Ben Fradj, Mohamed Kacem; Talbi, Emna; Bezrati, Ikram; Feki, Moncef; Bouassida, Anissa
Highlights: Metabolic syndrome is associated with an altered plasma adipokines profile. Adiponectin and omentin are inversely related to cardio-metabolic risk factors. Circulating leptin and chemerin are associated with a poor cardio-metabolic profile. Abstract: The study aimed to investigate association of circulating leptin, adiponectin, chemerin, and omentin-1 with metabolic syndrome (MetS) and cardio-metabolic risk factors in youths. Thirty eight young males were enrolled. Participants underwent anthropometric and blood pressure measures, and fasting blood sampling. Plasma leptin, adiponectin, chemerin, omentin-1 and insulin were measured by ELISA methods. Multiple linear regression models, adjusting for age, MetS traits, C-reactive protein (CRP) and homeostasis model assessment of insulin resistance (HOMA-IR), were applied to determine correlates for each adipokine. Eleven participants meet criteria of MetS. These individuals had higher leptin and chemerin and lower adiponectin plasma concentrations than those without MetS. Plasma leptin and chemerin were positively related, and adiponectin and omentin-1 were inversely related to cardio-metabolic traits. In multivariate models, predictors of leptin were age (β, 0.20, P = 0.01), abdominal obesity (β, 0.24, P = 0.06), raised blood pressure (β, 0.40, P = 0.01), raised triglycerides (β, 0.19, P = 0.01) and CRP (β, 0.31, P = 0.01). Chemerin was associated with abdominal obesity (β, 0.33, P = 0.09) and CRP (β, 0.29, P = 0.04), and adiponectin was associated with raised triglycerides (β, −0.26, P = 0.05), decreased HDL-C (β, −0.28, P = 0.06) and CRP (β, −0.48, P = 0.01). HOMA-IR (β, −0.39, P = 0.09) was the only predictor for omentin. MetS is associated with an altered plasma adipokines profile, with increased leptin and chemerin and decreased adiponectin circulating levels. These findings suggest a beneficial potential of adiponectin and omentin, but a detrimental potential of leptin and chemerin. Further research is needed to lighten the role of adipose tissue-derived adipokines in cardio-metabolic health.